Maize meiotic mutants with improper or non-homologous synapsis due to problems in pairing or synaptonemal complex formation - Golubovskaya, Inna N. (Oxford University Press, 2011)
During meiotic prophase homologous chromosomes find each other and pair. Then they synapse, as the linear protein core (axial element or lateral element) of each homologous chromosome is joined together by a transverse central element, forming the tripartite synaptonemal complex (SC). Ten uncloned Zea mays mutants in our collection were surveyed by transmission electron microscopy by making silver-stained spreads of SCs to identify mutants with non-homologous synapsis or improper synapsis. To analyse the mutants further, zyp1, the maize orthologue of the Arabidopsis central element component ZYP1 was cloned and an antibody was made against it. Using antibodies against ZYP1 and the lateral element components AFD1 and ASY1, it was found that most mutants form normal SCs but are defective in pairing. The large number of non-homologous synapsis mutants defective in pairing illustrates that synapsis and pairing can be uncoupled. Of the ten mutants studied, only dsy2 undergoes normal homologous chromosome recognition needed for homologous pairing. The dsy2 mutation fails to maintain the SC. ZYP1 elongation is blocked at zygotene, and only dots of ZYP1 are seen at prophase I. Another mutant, mei*N2415 showed incomplete but homologous synapsis and ASY1 and AFD1 have a normal distribution. Although installation of ZYP1 is initiated at zygotene, its progression is slowed down and not completed by pachytene in some cells and ZYP1 is not retained on pachytene chromosomes. The mutants described here are now available through the Maize Genetics Cooperation Stock Center (http://maizecoop.cropsci.uiuc.edu/).